ANALISIS PENGARUH KOREAN WAVETERHADAP EKSPOR, IMPOR DAN CADANGAN DEVISA INDONESIA PERIODE 2007-2016 - Putri Walianti Aprilia; Made Siti Sundari; Idfi Setyaningrum (Perpustakaan Universitas Surabaya, 2018)
Korean wave is a phenomenon has become an alternatif culture that consist principally of two froms of media, television serial or pop music (K-pop). Korean wave is one example of the succses of a country developing cultural and able to make the most for the welfare of the country. This study aims to determine the effect of Korean wave to Export, Import and Foreign exchange reserves during the period of 2007-2016. The method of analysis used is the Ordinary Least Square Method and Two Stage Least Square Method by using analytical tool to help process data is Eviews 9 progam. The result of analysis shows that Korean wave has positif influence to Import and has a negative influence to Export. This study also found if Import has positif influence to Foreign exchange reserves and Export has negative influence to Foreign exchange reserves.